État de siège: A dying domesticating colonialism? - HAGE, GHASSAN (American ethnologist, 2016)
ABSTRACT The sentiment of being “surrounded by barbarians” was once specific to settler‐colonial societies. But as the European refugee crisis made headlines in 2015, it became evident that this sentiment is gaining widespread currency in the Western world. Three developments lie behind its extension: first, the resurgence in the militarized Western appropriation of world resources and its colonial imaginary; second, the crisis in the order of the national borders that has regulated the exploitation of land, resources, and labor in the neocolonial era; and third, the ecological crisis, which equally manifests itself as a crisis in the order of the borders of domestication that defined the modern exploitation of nature. Analyzing the intersection of these social processes offers us important insights into some of the dominant dynamics of Western culture today. [settler colonialism, primitive accumulation, refugee crisis, national borders, ecological crisis, Agamben]